2010
DOI: 10.1111/j.1399-3046.2009.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect immunohistochemical evaluation of graft fibrosis and interface hepatitis after pediatric liver transplantation

Abstract: Fibrosis or IH following pediatric liver transplantation is recognized as major causes of graft loss, but the etiology remains unclear. To determine this issue, we used an indirect immunohistochemistry technique with post-transplant serum samples from recipients and normal human liver tissues from living liver donors, and the association between occult antibody reaction to the liver and the occurrence of fibrosis or IH was evaluated. Forty-three recipients were evaluated, and both hepatocytes and biliary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…This particularly applies to the pediatric population, in whom recurrent disease can largely be excluded as a cause of late graft dysfunction. Evidence in support of this suggestion includes the following: The frequent presence of autoantibodies/alloantibodies as well as other uncharacterized serum factors, which may react with donor hepatocytes and/or bile ducts The observation that previous episodes of rejection are a risk factor for IPTH …”
Section: Incidence Risk Factors and Possible Etiology Of Graft Hepamentioning
confidence: 99%
See 1 more Smart Citation
“…This particularly applies to the pediatric population, in whom recurrent disease can largely be excluded as a cause of late graft dysfunction. Evidence in support of this suggestion includes the following: The frequent presence of autoantibodies/alloantibodies as well as other uncharacterized serum factors, which may react with donor hepatocytes and/or bile ducts The observation that previous episodes of rejection are a risk factor for IPTH …”
Section: Incidence Risk Factors and Possible Etiology Of Graft Hepamentioning
confidence: 99%
“…The frequent presence of autoantibodies/alloantibodies as well as other uncharacterized serum factors, which may react with donor hepatocytes and/or bile ducts. (3,14,20) 2. The observation that previous episodes of rejection are a risk factor for IPTH.…”
Section: Incidence Risk Factors and Possible Etiology Of Graft Hepamentioning
confidence: 99%
“…Many paediatric cases are associated with the development of autoantibodies [12] or uncharacterized serum factors reacting with normal hepatocytes and/or biliary epithelial cells [139] or with features suggestive of rejection [135], suggesting that this is likely to represent a form of immune-mediated graft damage. This hypothesis is supported by the observation that treatment of IPTH with increased immunosuppression may prevent fibrosis progression [140] and by the suggestion, discussed earlier, that late rejection may present with ''hepatitic features'' resembling chronic viral or autoimmune hepatitis.…”
Section: Idiopathic Post-transplant Hepatitis (Ipth)mentioning
confidence: 98%
“…Several protocol biopsy–based studies have clearly shown an association between progressive liver fibrosis and IPTH,52, 53 which might represent a hepatitic variant of rejection53 or de novo AIH 54‐59. This is in contrast to other studies attributing progressive fibrosis in pediatric recipients to late manifestations of early technical or transplant‐related factors such as biliary strictures,50 cellular rejection,54, 60, 61 and late‐onset indolent antibody‐mediated rejection (AMR) 62. Late‐onset rejection with hepatitic features, IPTH, and de novo AIH are generally considered to be distinct entities, but emerging evidence suggests that they might contribute to an overlapping spectrum of immune‐mediated injury in long‐term survivors 39, 63.…”
Section: Special Concerns For Pediatric Recipientsmentioning
confidence: 96%